2017
DOI: 10.1177/0269216317744503
|View full text |Cite
|
Sign up to set email alerts
|

Dying persons’ perspectives on, or experiences of, participating in research: An integrative review

Abstract: Background:Conducting research with dying persons can be controversial and challenging due to concerns for the vulnerability of the dying and the potential burden on those who participate with the possibility of little benefit.Aim:To conduct an integrative review to answer the question ‘What are dying persons’ perspectives or experiences of participating in research?Design:A structured integrative review of the empirical literature was undertaken.Data sources:Cumulative Index Nursing and Allied Health Complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 30 publications
(110 reference statements)
2
68
0
1
Order By: Relevance
“…Participants' vulnerability must always be evaluated when planning and performing research (Moule et al, 2017;Ruyter et al, 2014). Cancer patients in the palliative phase and their families are considered to be a vulnerable group (Chen et al, 2014;Hanson et al, 2014;Sivell et al, 2015); their time is valuable, participation in research is burdensome, and the patients themselves will not benefit from the knowledge which is produced (Bloomer, Hutchinson, Brooks, & Botti, 2018;Ruyter et al, 2014;Sivell et al, 2015). Studies have shown that using words such as death and the palliative phase in the information letter can be perceived as burdensome (Gjertsen, 2009), and can unexpectedly reveal diagnoses and prognoses (Hickman, Cartwright, Nelson, & Knafl, 2012); therefore the terminology 'people living with cancer' was used in the information letter.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants' vulnerability must always be evaluated when planning and performing research (Moule et al, 2017;Ruyter et al, 2014). Cancer patients in the palliative phase and their families are considered to be a vulnerable group (Chen et al, 2014;Hanson et al, 2014;Sivell et al, 2015); their time is valuable, participation in research is burdensome, and the patients themselves will not benefit from the knowledge which is produced (Bloomer, Hutchinson, Brooks, & Botti, 2018;Ruyter et al, 2014;Sivell et al, 2015). Studies have shown that using words such as death and the palliative phase in the information letter can be perceived as burdensome (Gjertsen, 2009), and can unexpectedly reveal diagnoses and prognoses (Hickman, Cartwright, Nelson, & Knafl, 2012); therefore the terminology 'people living with cancer' was used in the information letter.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Studies have shown that using words such as death and the palliative phase in the information letter can be perceived as burdensome (Gjertsen, 2009), and can unexpectedly reveal diagnoses and prognoses (Hickman, Cartwright, Nelson, & Knafl, 2012); therefore the terminology 'people living with cancer' was used in the information letter. It has also been claimed that not researching vulnerable groups is unethical, since the objective of research is to obtain knowledge and promote quality in the health care service (Bloomer et al, 2018;Sivell et al, 2015). In order to reduce the risk of harm, the initial contact was made by health care personnel who knew the families and were able to evaluate the families' vulnerability (Hickman et al, 2012).…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the respect to their autonomy, patients should be given the choice to decide about their research participation by themselves (2,3). Denying patients and their family carers of this choice is deemed as unethical (1) and paternalistic (4) and can jeopardize the further development of evidence based palliative care.…”
Section: Introductionmentioning
confidence: 99%